2003
DOI: 10.1007/s00467-003-1220-3
|View full text |Cite
|
Sign up to set email alerts
|

ACE inhibition modulates transforming growth factor-? receptors in the young rat

Abstract: The renin-angiotensin system plays an important role in renal growth and development. Exposure of the neonate to angiotensin converting enzyme (ACE) inhibitors increases mortality and results in growth retardation and abnormal renal development. It has been demonstrated that ACE inhibition in the developing kidney reduces the renal expression of growth factors, which may account for renal growth impairment. This study was designed to investigate the relationship between renal growth impairment and the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Our previous studies demonstrated that ACE inhibition by enalapril decreased cellular proliferation in the developing rat kidney. The PCNA-positive proliferating cells were also decreased significantly in the same cortical tubular epithelial cells (12, 15). …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our previous studies demonstrated that ACE inhibition by enalapril decreased cellular proliferation in the developing rat kidney. The PCNA-positive proliferating cells were also decreased significantly in the same cortical tubular epithelial cells (12, 15). …”
Section: Discussionmentioning
confidence: 84%
“…Ang II inhibition by angiotensin converting enzyme (ACE) inhibitor in the developing rat kidney decreases the cellular proliferation and increases apoptosis, and this may account for neonatal renal growth impairment (7, 8, 12-15). These results suggest that the RAS is necessary for normal renal growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that ERMs can spontaneously resolve in cases of PVD occurrence, and this may happen when the ERM's adhesion to the posterior hyaloid membrane is stronger than its adhesion to the underlying ILM [76][77][78][79]. Since our patient was known to have an already complete PVD prior to the diagnosis of ERM and the intake of ARBs (candesartan) was the only evident discriminating factor that could have led to the spontaneous resolution of ERM, we hypothesize a molecular mechanism through which the fibrosis constituting the ERM could been affected and resolved by the molecular mechanism of ARBs (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Whether Ang II either mediates proliferation or rather hypertrophy depends on the renal cell type. All components of the RAS are developmentally regulated in renal organogenesis, and blocking the RAS in the developing kidney shows severe renal abnormalities and abnormal cellular turnover18). Ang II-induced growth effects are also implicated in the development of glomerulosclerosis and tubulointerstitial fibrosis and antagonizing these effects is a primary target of renoprotection modality in clinical nephrology.…”
Section: Physiologic Effects Of Angiotensin IImentioning
confidence: 99%